Experimental investigation on the failure characteristic and synergistic load-bearing mechanism of multi-layer linings for deep soft rock tunnels - Haibo Wang; Fuming Wang; Chengchao Guo; Lei Qin; Jun Liu; Tongming Qu (Underground Space)
Multi-layer linings have been widely used in deep rheological soft rock tunnels for the excellent performance in preventing large-deformation hazards. Previous studies have focused on the bearing capability of multi-layer lining, however, its failure characteristics and synergistic load-bearing mechanisms under high geo-stress are still unclear. To fill the gap, three-dimensional geomechanical model tests were conducted and synergistic mechanisms were analysed in this study. The model test was divided into normal loading, excavating, and overloading stages. The surrounding rock deformation was monitored by using an improved high-precise extensometer measurement system. Results show that the largest radial deformation appears on the sidewall, followed by the floor and vault during the excavating stage. The relative convergence deformation of sidewalls springing reaches 1.32 mm. The failure characteristics of the multi-layer linings during the overloading stage undergo an evolution of stability, crack initiation, local failure, and collapse, with a safety factor of 1.0–1.6, 1.6–2.0, and 2.0–2.2, respectively. The synergistic load-bearing mechanism analysis results suggest that the early stiffness and late yielding deformation capacity of large deformation support measures play important roles in stability maintenance both in the construction and operation of deep soft rock tunnels. Therefore, the combination of yielding support or a compressible layer with reinforced support is recommended to mitigate the effect of the high geo-stress.